House Flies: Manure, Media, and Microbes - Adams, Porter; McCoy, Christie; Thomson, Jessica L.; Nayduch, Dana (My University, 2018)
This study was conducted to determine if there is a difference in bacterial abundance in house flies based on sex and rearing environment (manure versus artificial media) for house flies. This is important in determining the effectiveness of the facilities where the flies are being raised. Although, previous studies have shown differences in bacterial abundance between male and female house flies, it still remains unknown whether there is a discrepancy in bacterial abundance between rearing environments in the lab. We hypothesized that there would be a greater abundance of bacteria in females than males and a greater bacterial abundance in the manure environment than the artificial media. We determined that there was no significant difference between house fly sex or the environments in which they were raised. These results are meaningful because they introduce evidence of forced interaction that could skew the bacterial counts. In the future, the results would be more telling with a larger sample size. !
Keywords: Fall 2018